Export Analysis of Indonesian Vehicles (HS 87) To 9 Developing Countries Using The Gravity Model Approach - Fabian Crisandy E.D.; Wijaya, Riko Setya; Perdana, Putra (International Forum of Researchers and Lecturers, 2025)
This study examines the factors influencing Indonesia’s motor vehicle exports to nine developing countries using the gravity model approach with long-term and short-term panel data. The variables analyzed include the Gross Domestic Product (GDP) of partner countries, exchange rates, economic distance, and trade cooperation agreements. The data are analyzed using the Error Correction Model (ECM) to capture short-term dynamics and long-term relationships. The long-term results show that partner countries’ GDP has a significant positive effect on Indonesia’s vehicle exports, indicating that economic growth in partner countries increases demand for Indonesian automotive products. Conversely, exchange rates and economic distance have significant negative effects, suggesting that depreciation of partner currencies and economic disparities reduce export volumes. Trade cooperation agreements do not have a significant impact in the long term. In the short term, changes in GDP continue to have a significant positive effect, while exchange rates maintain a significant negative impact on exports. Economic distance and trade agreements are not significant in the short term. The significant and negative error correction term (ECT) confirms the existence of an adjustment mechanism toward long-term equilibrium. This study highlights the importance of partner countries’ economic growth and exchange rate stability in supporting Indonesia’s vehicle exports to developing countries, as well as the need to address structural barriers to improve long-term competitiveness.